Increasing Awareness of Healthy Internet Youth in Miru Village, Lamongan Regency Using Internet of Things-Based Blogs - Maria Novita Apriyani; Miko Aditiya Suharto; Acmad Khozin Baharudin (Future Science, 2022)
The occurrence of massive changes in the realm of human life, one of which requires humans to be attached to cyber technology. Today's society, especially the younger generation, cannot be kept away from using the internet. Internet of Things makes Indonesia an opportunity to become one of the countries that can develop this technology. Like a double-edged coin, these opportunities can pose various threats including misuse of personal data, the emergence of the development of cybercrime with the latest tools such as cracking, illegal access, etc. The formulation of the problem that can be put forward by the author is (1) how is the impact of Internet of Things technology on today's young generation (2) how is the effectiveness of Internet of Things technology for the younger generation. The implementation of community service activities related to healthy and intelligent internet education based on the Internet of Things consists of 2 (two) parts, a literature study related to the activity title, namely healthy and intelligent internet education based on the Internet of Things, coordinating with the Miru Village government, Sekaran District, Lamongan Regency. The second stage in the implementation of community service activities was carried out offline on Thursday, July 14, 2022 at the Miru Village Hall which was attended by 20 Miru Village youth groups from several vulnerable groups aged 17-30 years. The result of this research is that cybercrime is closely related to transnational crime. The emergence of new criminal acts as part of the negative impact of Internet of Things technology such as online gender-based sexual violence crimes, theft of personal data and cyberbullying in Indonesia's young generation makes generation Z and millennial generation need education on how to use the internet in a healthy, intelligent and responsible manner.